Physiological aspects of milk ejection : a thesis submitted in partial fulfilment of the requirements for the Degree of Master of Agricultural Science in the University of New Zealand - Brumby, Peter James (Massey University, 1952)
During the latter part of the last century, a number of physiologists conceived the idea that the functions of the mammary growth and milk secretion were under the control of the nervous system. As a consequence, many experiments were carried out with the object of elucidating the role of the nervous system in lactation; these culminating in the classic experiments of Ribbert. In the year 1898, this man succeeded in transplanting mammary tissue from the inguinal region of the guinea pig to an area behind the ear, thus demonstrating that the mammary gland could grow, and to a limited extent function, independent of nervous connections. Attention was then focused on the possibility of a purely endocrine control of the mammary gland, a concept that has given rise to much valuable knowledge by virtue of the experimentation it has stimulated. However a third phase in the history of research into mammary gland function is now being entered upon. As with a general tendency of investigations in endocrinology as a whole, integrations are being sought between endocrine and nervous mechanisms. [FROM INTRODUCTION]
Keywords: Dairy cattle -- Physiology; Lactation; Hormones